2022
DOI: 10.34133/2022/9893418
|View full text |Cite
|
Sign up to set email alerts
|

High-Harmonic Generation and Correlated Electron Emission from Relativistic Plasma Mirrors at 1 kHz Repetition Rate

Abstract: We report evidence for the first generation of XUV spectra from relativistic surface high-harmonic generation (SHHG) on plasma mirrors at a kilohertz repetition rate, emitted simultaneously with energetic electrons. SHHG spectra and electron angular distributions are measured as a function of the experimentally controlled plasma density gradient scale length Lg for three increasingly short and intense driving pulses: 24 fs and a0=1.1, 8 fs and a0=1.6, and finally 4 fs and a0≈2.1, where a0 is the peak vector po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…[16][17][18] In addition, plasmonic mirrors have also proven to be feasible for achieving ultrafast lasers. [19] Consequently, nanomaterials become competitive SAs, which currently are widely used in broadband ultrafast photonics. [20][21][22] There are multiple types of nanomaterials applied in ultrafast photonics.…”
Section: Fabrication and Applications Of Heterostructure Materials Fo...mentioning
confidence: 99%
“…[16][17][18] In addition, plasmonic mirrors have also proven to be feasible for achieving ultrafast lasers. [19] Consequently, nanomaterials become competitive SAs, which currently are widely used in broadband ultrafast photonics. [20][21][22] There are multiple types of nanomaterials applied in ultrafast photonics.…”
Section: Fabrication and Applications Of Heterostructure Materials Fo...mentioning
confidence: 99%
“…The research on lasers has attracted much attention worldwide since 1960s. [225][226][227][228] The pulsed fiber lasers have aroused much interest and have played important roles in areas ranging from scientific research to industrial and medical applications over the past few decades. The passively mode-locking and Q-switching technologies with the insertion of a SA into the laser cavity to transform a continuous wave into pulsed laser output attract much attention.…”
Section: Applications Of Emerging Nanostructured Materials As the Sas...mentioning
confidence: 99%
“…The development of optical fiber-based devices has come a long way, with ever-expanding interest in sensing [23][24][25][26][27]. Furthermore, recent experimental and theoretical studies [28] have shown that lasers capable of operating at ultrafast speeds can also be used to realize various real-life applications, such as controlling the wettability of material surfaces, in turn realizing applications such as corrosion control, water harvesting and anti-icing [29] as well as exploring complex soliton interaction dynamics [30,31], harmonic generation [32] and generating terahertz pulses [33]. These potential applications have driven intense research efforts to develop ultra-fast pulsed fiber lasers, particularly on laser cavities using rare-earth doped optical fibers.…”
Section: Introductionmentioning
confidence: 99%